Delayed spontaneous resolution of a double anterior chamber following deep anterior lamellar keratoplasty (DALK) - Poramaporn Luangprasert; Passara Jongkhajornpong; Kaevalin Lekhanont; Manachai Nonpassopon; Varintorn Chuckpaiwong (BMC Ophthalmology)
Abstract Background This study reports a rare case of delayed spontaneous resolution of double anterior chambers (AC) resulting from non-rhegmatogenous Descemet membrane detachment (DMD) after deep anterior lamellar keratoplasty (DALK). Currently, management guidelines for this condition have not been established. Case presentation A 65-year-old woman with lattice corneal dystrophy underwent uncomplicated DALK, during which an unrecognized type 2 big bubble was present. On postoperative day 1, a total DMD was observed, and descemetopexy was attempted. After an unsuccessful air-filled descemetopexy, we opted for observation without further intervention. Spontaneous reattachment of Descemet membrane with a clear cornea was achieved at 3 months postoperatively. The endothelial cell count was 2,165 cells/ mm2. Conclusions The spontaneous resolution of double AC in patients with DMD without visible perforation after DALK suggests that a “wait and observe” approach can be a reasonable and effective management strategy.